The Development of Electricity Markets in the Euro-Mediterranean Area : Trends and Prospects for Liberalization and Regional Integration - Muller-Jentsch, Daniel (Washington, DC: World Bank, 2013)
The main objective of this document is to map key policy issues that need to be addressed to successfully implement energy sector reform at the national, and regional levels, and, provides an overview of global, European, and Mediterranean trends, aiming at facilitating the dissemination of best practices. Chapter I describes international best practices in the design of legal, regulatory, and institutional sector framework, which include corporatization, and restructuring of state-owned energy utilities; separation of regulatory and operational functions, by creating coherent regulatory frameworks, establishing independent regulators, and promoting competition; engaging the electricity industry into generation, transmission, distribution, and trade; introduction of competition in generation, and trade, and, in the regulation of monopolistic activities; promotion of private participation; and, reduction of subsidies, and balance of tariffs. Chapters II and III examine power sector reform in the European Union (EU), and power sector policies of the Mediterranean partners, reviewing liberalization, regulatory institutions, and the development of electricity markets, and power trading in the EU. It specifies that despite recent progress, the main structural flaw of energy reform in the Mediterranean region, has been the lack of liberalization, and effective regulation, contrasting sharply with EU reforms, where the focus for electricity, and gas has been the introduction of competition. Chapter IV proposes an agenda for regional change, through sector reforms, promotion of energy policy, economic analysis, and interconnection, through technical assistance, and financial support, to create integrated, competitive cross-borders for power markets.